2011
DOI: 10.5251/abjna.2011.2.2.341.349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical refining steps on the minor and major components of cottonseed oil

Abstract: During chemical refining steps (neutralization, bleaching and deodorization) of crude cottonseed oil (CSO), minor and major components, namely, tocopherols, sterols and fatty acids were evaluated by HPLC and GLC. HPLC analysis of total tocopherols (T) revealed that loss in these components were 7.12, 12.28 and 18.47 % in neutralized, bleached and deodorized oil respectively. On the other side, quantitative GLC analysis of sterols (as trimethylsilyl derivative, TMS), showed that the losses were 5.6, 8.7 and 16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
0
19
1
3
Order By: Relevance
“…In other oils total sterol content was slightly reduced in cotton seed oil (8.7% according to El-Mallah et al (2011). In other study authors observed a reduction of 1.3, 8 and 18.5% in corn, soybean and rapeseed respectively in the total sterol content (Ferrari et al, 1996).…”
Section: Bleachingmentioning
confidence: 77%
“…In other oils total sterol content was slightly reduced in cotton seed oil (8.7% according to El-Mallah et al (2011). In other study authors observed a reduction of 1.3, 8 and 18.5% in corn, soybean and rapeseed respectively in the total sterol content (Ferrari et al, 1996).…”
Section: Bleachingmentioning
confidence: 77%
“…These vegetable oils all have many well-known brands and are obtained by different oil processing technologies. It is well known that the oil extraction method, refining degree, and material source affect the content and composition of phytosterols [26,27,28,29]. The purpose of this study was to investigate the phytosterol contents of different kinds of vegetable oils.…”
Section: Introductionmentioning
confidence: 99%
“…The peroxide value of oil containing antioxidants was lower than peroxide value of oil which contained no additive (control). From the results, it showed that peroxide value of refined oil reached a higher value than crude oil because natural antioxidants such as total tocopherol, sterol and carotenoid had been lost during refining [16]. Peroxide value of the samples having sesame and sunflower extracts were less than propyl gallate but more than tert-butylated hydroxyquinone (TBHQ).…”
Section: Resultsmentioning
confidence: 87%